Karakteristik Peternak Kambing Di Kecamatan Bikomi Utara Kabupaten Timor Tengah Utara - Seran, Lorensia; Beyleto, Veronika Yuneriati; Sahala, Josua; Simamora, Ture; Pasi, Maria Selfiana (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study is to identify the characteristics of the goat farmer in the north central timor district of the bikomi region. The study has been carried out in the months of juni-september 2024 in the villages of banain a, banain b, banain c, faenake, sainoni, tests, and napan denunciations north of timorr central district of Syria. The number of samples taken in this study is 99 individuals. The type of data used in the study are primary and secondary data. Analysis shows that the characteristic of the farmer in the age category is dominated by the breeders with a particularly productive 21-65 years of 93 people (94.38%). The gender of the farmer shows that the male breeders are as many as 56 (56.6%). Formal education levels for those in the low category graduate school by 62 (62.6%). The level of nonformal education for respondents in the seven villages who have never had training is as many as 89 (89.9%). The type of work of respondents was dominated by the work of a farmer of 52 people (52.5%). The average farmer's experience is dominated by a very low category of 0-5 years of which is 61 people (61.6%). The reduced ownership of respondents in the low category of 1-10 as many as 87 (87.9%). A cosmopolitan rancher of 99 (100%). The respondents' educational motivation is to increase additional income and income.